E-COURSE MANAGEMENT WITHIN MOODLE IN HIGHER EDUCATION: TECHNOLOGICAL AND PEDAGOGICAL ISSUES - Gorbāns, Imants; Bierne, Jekaterina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
E-course management could be reflected both pedagogically, which implies analysis of teacher’s role as course manager, and administratively, making course activities traceable for estimation and institutional control. The article presents the results of Moodle log data analysis at higher education institutions in Latvia. Analysis is made in order to reveal Moodle log data opportunities and restrictions as an instrument, which could be purposefully used for course management both in administrative and pedagogical sense. Moodle log data analysis, which is showing time, activities and additional information about Moodle interactive tools usage, has been compared to teachers’ self-report survey results about their e-course management activities within Moodle. The study shows that teachers are tended to overestimate their course management activities’ frequency within Moodle comparing to lag data. Possibility to analyse Moodle log data by teachers and higher education institution administration could help to improve e-courses management, which is significant factor for improving learning outcomes.